High-Resolution Digital Elevation Modeling from TLS and UAV Campaign Reveals Structural Complexity at the 2014/2015 Holuhraun Eruption Site, Iceland - Müller, Daniel; Walter, Thomas R.; Schöpa, Anne; Witt, Tanja; Steinke, Bastian; Gudmundsson, Magnús T.; Dürig, Tobias (Frontiers in Earth Science, 2017)
Fissure eruptions are commonly linked to magma dikes at depth, associated with elastic and anelastic surface deformation. Elastic deformation is well described by subsidence above, uplift and lateral widening perpendicular to the dike plane. The anelastic part is associated with the formation of a graben, bordered by graben parallel faults that might express as sets of fractures at the surface. Additionally secondary structures, like push ups, bends and step overs yield information about the deforming domain. The formation of such structures associated with fissure eruptions, however, is barely preserved in nature because of the rapid erosion or sediment coverage. Therefore, simple normal fault displacements are commonly assumed at dikes. At the 2014/2015 Holuhraun eruption sites (Iceland), evidence is increasing that the developing fractures are showing variations in their displacement modes. In an attempt to investigate these variations, a fieldwork mapping project combining Terrestrial Laser Scanning (TLS) and Unmanned Aerial Vehicle (UAV) based aerophoto analysis was realized. From this data, we generated locally high resolution Digital Elevation Models (DEMs) and a structural map that allows for identification of kinematic indicators and assessing particularities of the observed structures. We identified 315 fracture segments from satellite data. For single segments we measured strike directions including the amount of opening and opening angles, indicating that many of the measured fractures show transtensional dislocations. Out of these, 81 % are showing significant left-lateral slip, only 17% right-lateral slip and 2% pure tensile opening. We show that local complexities in the fracture traces and geometries are closely related to variations in the transtensional opening direction. Moreover, we identified local changes in fracture azimuths and offsets close to eruption sites, which we speculate to be associated with geometrical changes in the magma feeder itself. Results highlight that opening of fractures associated with an erupting fissure commonly show transtensional modes having both, left-lateral and right-lateral slip, with important implications for interpreting the expression of surface structures at rift zones elsewhere. Results further highlight the great value of UAV based high resolution data to contribute to the integrity of observations of structural complexities at local geologic events.